Agricultural tractor electrical propulsion concept - Tero Lappalainen; Ilya Petrov; Juha Pyrhönen (Energy Conversion and Management: X)
Although the limited energy density of energy storages currently slows down the electrification of agricultural tractors, the wide rotation speed range and excellent torque of electric machines are of particular interest in propulsion research and development in the field. Modern tractor propulsion systems must be able to comply with a variety of applications from low-speed high-torque to moderate and high-speed applications. Two distinct operating points may be highlighted. Ploughing or cultivating are typically performed at speed less than 10 km/h, whereas transportation takes place at speeds between 50–60 km/h. In both cases, constant high-power operation is demanded. This differentiates a tractor’s electric drive cycle totally from e.g. a passenger car electric drive load. A concept-level examination into the electrical propulsion suitability for an agricultural tractor’s rear axle is presented. Since there are several options for the type of propulsion motor, a rough pre-selection process is first performed. Selected machine types are then studied against the required pulling performance curve by employing applicable ratios for planetary and final drive gear reduction. Machine efficiencies are analytically calculated at operating points and further validated with 2D efficiency maps for the best candidates. Magnetic circuits are subjected to a mechanical quantification and a corresponding cost structure is calculated with publicly available commodity prices. Finally, a candidate for a prototype building and testing phase is proposed.